2016
DOI: 10.1093/geronb/gbw072
|View full text |Cite
|
Sign up to set email alerts
|

Subjective Age Across the Life Span: A Differentiated, Longitudinal Approach

Abstract: Our results provide support for a multidimensional view of subjective aging experiences. They highlight the importance of a differentiated investigation of subjective aging constructs and their relations for understanding how these variables shape the aging process.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
50
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 60 publications
(56 citation statements)
references
References 43 publications
5
50
1
Order By: Relevance
“…Furthermore, the association between subjective age and psychological and behavioral symptoms of dementia deserves attention. Finally, based upon recent evidence of the multidimensionality of subjective age (Kornadt et al, in press), future research could examine whether specific facets may be more predictive of cognitive impairment and dementia.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, the association between subjective age and psychological and behavioral symptoms of dementia deserves attention. Finally, based upon recent evidence of the multidimensionality of subjective age (Kornadt et al, in press), future research could examine whether specific facets may be more predictive of cognitive impairment and dementia.…”
Section: Discussionmentioning
confidence: 99%
“…A further possible limitation is use of a single item to measure subjective age. Some researchers have argued that the construct is multidimensional so it may not be captured in a single measure as there may other domains of subjective age which may reflect more upon factors, such as, physical or societal changes (Diehl et al, 2015;Kastenbaum et al, 1972;Kornadt et al, 2016;Kotter-Grühn et al, 2016). Recent studies have also indicated that subjective appraisals of age are quite changeable on a day to day, or even a moment to moment basis (Kotter-Grühn et al, 2015).…”
Section: Strengths and Limitationsmentioning
confidence: 99%
“…In fact, older adults have a tendency to assimilate and identify with middle-aged adults and to contrast and distance themselves from older adults [27]. In addition, research shows that negative age stereotypes elicit feeling younger and distancing oneself from the group of older people [28, 29]. Research on self-protective processes has shown that age-group dissociation (i.e., “the tendency to put psychological distance between oneself and similarly aged people,” see Weiss and Lang [29, p. 154]) buffers older adults against the detrimental consequences of negative views of aging (e.g., [30]).…”
Section: Contrast – Differentiating the Self From Societal Perceptionmentioning
confidence: 99%